(3GdCQHYjf aj GdESdGe ef GdCMGOjK GdfHhjI Yf CQHYjf ef eTGjN GdESdGes - (3CMeO Hf CHj HcQ CMeO GdMfHdj GdbGOQj,J (B844 (3g` s ((3eSLO GdfGQfLg(B_ (3HMdH GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGJHGY SfI fHjfG eMeO SjO GdeQSdjf GdMOjK GdChd Yf eTGjN efge SjOfG hTjNfG GdGeGe GdYdGeI bGVi GdbVGg TgGH GdOjf GHh GdYHGS CMeO s
(3BNQgG (B:s
(3hgh GdfHi Edi GdGfGe JMeO jG SjOi GQLhc JZaQ RdJi CUHMJ HGdPfhH GfTOfjgG ai Sfg SHY hKdGKjf heGjg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs